Morphology of the Great Cardiac Vessels in Egyptian Fruit Bat (Rousettus aegyptiacus) - Younes Kamali; Farangis Ghasemi (Negah Institute for Scientific Communication, 2021)
Introduction: The purpose of this study was to describe the anatomic appearance of great cardiac vessels in the Egyptian fruit bat (Rousettus aegyptiacus) as a common bat living in the southern region of Iran.  Methods: Five Egyptian fruit bats with a Mean±SD body mass index (BMI) of 123.04±0.08 g were selected and studied. Results: The aortic arch (transverse arch) cranial to the heart gives rise to the right and left brachiocephalic (innominate) arteries, each of which immediately divides into common carotid and subclavian arteries. The aortic arch continues caudally on the dorsal side of the heart, inclines to the left of the median plane as the dorsal aorta. The ligamentum arteriosum connecting the dorsal aorta to the pulmonary trunk is seen a few millimeters caudal to the origin of the left brachiocephalic artery. The arrangement of the great veins, including two anterior venae cavae, resembles that found in birds rather than mammals. A left azygos vein entered dorsally to join the left anterior vena cava. The opening of the right anterior vena cava is in the dorsal part of the right atrium; the opening of the left anterior vena cava, similar to the coronary sinus, is at the caudal part of the right atrium. The posterior vena cava opens into the right atrium dorsal and cranial to the entrance of the left anterior vena cava. Conclusion: The evolution in the morphology mentioned above is in accordance with the flight requirements of bats.